2018
DOI: 10.1029/2018gl079572
|View full text |Cite
|
Sign up to set email alerts
|

Future Nuisance Flooding in Norfolk, VA, From Astronomical Tides and Annual to Decadal Internal Climate Variability

Abstract: Increasing sea level rise will lead to more instances of nuisance flooding along the Virginia coastline in the coming decades, causing road closures and deteriorating infrastructure. These minor flood events can be caused by astronomical tides alone, in addition to internal climate variability on annual to decadal timescales. An assessment of nuisance flooding from these two effects is presented up until the year 2050 for Norfolk, Virginia. The analysis of water levels indicates that nuisance flooding from tid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
0
21
0
3
Order By: Relevance
“…Previous studies have reported on vulnerable sites for coastal subsidence and short-term sea level rise, including Hampton Roads, Virginia [14], New York City [15], Taiwan [16], and North Carolina [17]. Hence, the estimation and correction of the local ground motion at and around the tide gauges is important to minimize uncertainties in the local and global sea level changes observed [18][19][20][21][22][23]. In recent decades, long-term glacial adjustments were quantified using historical variations and climate models for the reconstruction of sea level records [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported on vulnerable sites for coastal subsidence and short-term sea level rise, including Hampton Roads, Virginia [14], New York City [15], Taiwan [16], and North Carolina [17]. Hence, the estimation and correction of the local ground motion at and around the tide gauges is important to minimize uncertainties in the local and global sea level changes observed [18][19][20][21][22][23]. In recent decades, long-term glacial adjustments were quantified using historical variations and climate models for the reconstruction of sea level records [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, understanding the drivers of the short-term swings that occur about the long-term trend would aid in planning efforts as high-tide flooding at the coast continues to increase (e.g., ref. 17).…”
mentioning
confidence: 99%
“…However, projections of mean sea level rise on multidecadal and longer time scales (Kopp et al 2014(Kopp et al , 2017 alone are insufficient to anticipate future coastal flood risk. Also important are sea level fluctuations at decadal and shorter periods, which can superimpose on longer-term changes, temporarily ameliorating or exacerbating coastal risk (Burgos et al 2018;Dangendorf et al 2016;Long et al 2020;Ray and Foster 2016;Sweet et al 2017). This motivates a detailed investigation of mean sea level variation in the Persian Gulf on decadal and shorter time scales-what are the dominant magnitudes, scales, and mechanisms?…”
Section: Introductionmentioning
confidence: 99%